2015
DOI: 10.1021/acsphotonics.5b00104
|View full text |Cite
|
Sign up to set email alerts
|

Tunable 3D Plasmonic Cavity Nanosensors for Surface-Enhanced Raman Spectroscopy with Sub-femtomolar Limit of Detection

Abstract: Metallic nanohole arrays (NHAs) with a high hole density have emerged with potential applications for surface-enhanced Raman spectroscopy (SERS) including the detection of analytes at ultra-low concentrations. However, these NHA structures generally yield weak localized surface plasmon resonance (LSPR) which is a prerequisite for SERS measurements. In this work, a compact three-dimensional (3D) tunable plasmonic cavity with extraordinary optical transmission properties serves as a molecular sensor with sub-fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 49 publications
(105 reference statements)
0
59
0
Order By: Relevance
“…[1][2][3][4][5] Raman enhancement is engineered by tuning SERS substrate design parameters such as elemental composition; the size and shape of nanoscale elements; close-range interparticle spacing responsible for hot spots; and patterning of solid substrates that can include ordered and random hierarchies across short, long, and multiple length scales. 1,3,[6][7][8][9][10] Physical structure of the SERSactive metal layer-either its inherent structure or the structure imposed upon it by an underlying support layer-is a critical and performance-determining factor. Considerable effort has been devoted to crafting a host of solid-supported SERS substrates, with results that inspire further efforts to improve and expand fabrication options, sensing capabilities, and sensing performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Raman enhancement is engineered by tuning SERS substrate design parameters such as elemental composition; the size and shape of nanoscale elements; close-range interparticle spacing responsible for hot spots; and patterning of solid substrates that can include ordered and random hierarchies across short, long, and multiple length scales. 1,3,[6][7][8][9][10] Physical structure of the SERSactive metal layer-either its inherent structure or the structure imposed upon it by an underlying support layer-is a critical and performance-determining factor. Considerable effort has been devoted to crafting a host of solid-supported SERS substrates, with results that inspire further efforts to improve and expand fabrication options, sensing capabilities, and sensing performance.…”
mentioning
confidence: 99%
“…Considerable effort has been devoted to crafting a host of solid-supported SERS substrates, with results that inspire further efforts to improve and expand fabrication options, sensing capabilities, and sensing performance. 1,3,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Top-down nanofabrication using conventional and unorthodox approaches can produce exquisitely structured substrates, but can require substantial practitioner expertise along with expensive, specialized, and complicated instrumentation, and can moreover substantially limit the palette of fabrication materials. SERS substrates developed outside the material and processing constraints of conventional micro-and nanofabrication have been compelling.…”
mentioning
confidence: 99%
“…It has been demonstrated that in 2D arrays with dimensions close to wavelength, diffraction occurs and yields modes that can be assigned to the lattice periodicity along the X ‐ and Y ‐directions . In our system, the periodic nanohole arrays on gold film result in momentum matching between the in‐plane wave vectors of the incident light and the surface plasmon,ksptrue→=(ω/c) sinθ±muxtrue→±nuytrue→, where ω is the frequency of the incident light, c is the speed of the light, θ is the incident angle of light, m and n are integers expressing the scattering mode indices, |uxtrue→| = |uytrue→| = (4π/(3a)) are the reciprocal lattice wave vectors along x ‐direction and y ‐direction, and a is the period of nanohole arrays.…”
Section: Resultsmentioning
confidence: 89%
“…Many kinds of new methods have been proposed for surface nanopatterning . A variety of nanopatterns such as nanorod array, nanohole array, nanopyramid array, nanoflower array, and nanostar array have been fabricated as SERS substrates by lithography techniques (e.g., ion‐beam lithography, nanoimprint lithography, and nanosphere lithography (NSL)). Among them, NSL is a prominent method as it is able to cost‐efficiently fabricate ultrasensitive SERS substrates with high density of hot spots .…”
Section: Assignment Of Bands In Sers Spectra Of Aβ Oligomers N = Strmentioning
confidence: 99%